Factors Related to Seeking Help in People with Mental Disorders - Ruliyani Manumba; Achir Yani Syuhaimie Hamid (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
The prevalence of mental disorders is increasing, without being followed by the behavior of seeking help for people with mental disorders. Delay in seeking help can worsen symptoms, social and cognitive functions, and recovery of people with mental disorders. This paper aims to determine the factors associated with seeking help in people with mental disorders. This study using systematic review by searching articles in electronic database: PubMed, ProQuest, EBSCO, Science Direct, SpringerLink, Taylor & Francis, Wiley Online, and Scopus. Search results using the keywords help-seeking, mental illness, mental disorder, psychosis, schizophrenia were found in 2347 articles. After being filtered based on inclusion criteria, namely research articles that are relevant to the purpose of writing, free full text, English language, and published in 2015-2020 produced 61 articles. The same article was later issued and produced 33 articles. Articles that are not research results or review articles and articles that focus on problems or conditions other than target conditions such as emotional mental disorders are excluded. Analysis of 14 articles found several factors related to seeking help in people with mental disorders. These factors include stigma, knowledge and beliefs, accessibility, and conditions of health services, social environment, demographic characteristics, and severity.